2016
DOI: 10.1021/acscatal.6b01275
|View full text |Cite
|
Sign up to set email alerts
|

Synergy and Anti-Synergy between Palladium and Gold in Nanoparticles Dispersed on a Reducible Support

Abstract: Highly active and stable bimetallic Au–Pd catalysts have been extensively studied for several liquid-phase oxidation reactions in recent years, but there are far fewer reports on the use of these catalysts for low-temperature gas-phase reactions. Here we initially established the presence of a synergistic effect in a range of bimetallic Au–Pd/CeZrO4 catalysts, by measuring their activity for selective oxidation of benzyl alcohol. The catalysts were then evaluated for low-temperature WGS, CO oxidation, and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 72 publications
(128 reference statements)
10
79
1
Order By: Relevance
“…The Au 4f region (Supporting Information, Figure S8) gives valuable information on the form of Au present in the catalyst and is comprised of three distinct species; namely Au 0 (84.0 eV) and Au 3+ (86.1 eV), and a species at 85.0 eV. The assignment of the latter species, denoted Au 0 *, remains controversial with some studies attributing it to small Au NPs or clusters– whereas others relate it to positively charged Au species . Our microscopy supports an assignment of the Au 0 * species as small Au NPs or clusters.…”
Section: Figuresupporting
confidence: 71%
“…The Au 4f region (Supporting Information, Figure S8) gives valuable information on the form of Au present in the catalyst and is comprised of three distinct species; namely Au 0 (84.0 eV) and Au 3+ (86.1 eV), and a species at 85.0 eV. The assignment of the latter species, denoted Au 0 *, remains controversial with some studies attributing it to small Au NPs or clusters– whereas others relate it to positively charged Au species . Our microscopy supports an assignment of the Au 0 * species as small Au NPs or clusters.…”
Section: Figuresupporting
confidence: 71%
“…may indicate the presence of either oxidised gold species (Au δ+ ) or very small gold nanoparticles not seen in the HDAAF-STEM images. 43,44 The Pd (3d 5/2 ) spectra clearly indicates that both metallic palladium (Pd 0 ) and Pd δ+ species are present in the analysed catalyst samples.…”
mentioning
confidence: 93%
“…can be attributed to the electronic modification of Au species by Pd, and is indicative of the close interaction between the Au and Pd atoms, and the formation of Au-Pd alloys. 43 It can also be observed that the magnitude of the shift in the B.E. varies between the different catalyst samples.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…2 yield was calculated only for liquid products of glycerol oxidation which were in the solution after reaction. 3 TOF was calculated as the number of glycerol moles reacted on one mole of gold per one hour (after 5 h of the reaction).…”
Section: Catalytic Activity-glycerol Oxidationmentioning
confidence: 99%